Inflammation-driven mechanisms in endometrial cancer: pathways from inflammatory microenvironment remodeling to immune escape - Tan, Zhaoping; Sheng, Binyue; Chen, Lu; Dong, Hong; Deng, Yaqin; Li, Yunyun; Liu, Cong; Wang, Han; Yang, Zi; Xie, Ting; Huang, Yanming (Frontiers in Immunology, 2025)
The progression of endometrial cancer (EC) is significantly affected by the inflammatory microenvironment (IME), which is essential for facilitating immune evasion and developing resistance to therapeutic interventions. Components that promote immune suppression, such as regulatory T cells (Tregs), macrophages associated with tumors (TAMs), cytokines like interleukin-10 (IL-10) and transforming growth factors-beta (TGF-β), are crucial in establishing a favorable microenvironment for tumor growth. TAMs with a M2-like phenotype promote angiogenesis and inhibit antitumor immunity through the secretion pro-tumorigenic factor. Further, metabolic shifts in the extracellular matrix and structural modifications of the extracellular matrix (ECM) inhibit the infiltration of cytotoxic T lymphocytes (CTLs), thereby strengthening mechanisms of immune evasion. Inflammatory signaling pathways, such as interleukin-6/janus kinase/signal transducer and activator of transcription 3 (IL-6/JAK/STAT3) and NF-κB/tumor necrosis factor-alpha (TNF-α/NF-κB), also stimulate the expression immune checkpoint molecules, such as programmed cell death protein 1 (PD-1). Novel interventions aimed at modulating immune checkpoints, inhibiting TGF-β signaling, and altering metabolic circuits are under investigation and offer potential to counteract immune suppression and enhance therapeutic success. Nevertheless, significant obstacles remain, including intratumoral heterogeneity, fluctuating immune dynamics, and the absence of dependable biomarkers. Advancements in single-cell analysis and spatial transcriptomics are anticipated to unveil actionable molecular patterns and support the development of individualized strategies to interrupt immune evasion and therapeutic resistance in EC. These advances offer promise for personalized immunotherapy approaches that could significantly improve outcomes in endometrial cancer patients.